Modern Testing Techniques for Structural Systems Dynamics and Control - Bursi, Oreste S.; Wagg, David; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2008)
The articles in this book describe new developments in the area of structural testing, particularly those based upon the principle of fusing numerical and experimental methods such as real-time dynamic substructuring and hardware-in-the loop testing. In addition to the hybrid methods, chapters on the latest develoments in more established techniques, such as shaking table testing, provide a completely up-to-date survey of structural testing methods. The book is characterized by a multidisciplinary nature of the work that integrates cutting-edge research from the fields of non-linear dynamics, automatic control, numerical analysis, system modelling and mechatronics.
Computational Techniques for Simulation of Monolithic and Heterogeneous Structural Dynamic Systems -- A State Space Approach to System Identification -- A Review of Ground Motion Record Selection Strategies for Dynamic Structural Analysis -- Shaking Table Testing -- Continuous PsD Testing With Substructuring -- Real-Time Hybrid Testing Techniques -- Real-Time Testing With Dynamic Substructuring.
Keywords: Mechanics; Mechanics, Applied; Solid Mechanics